2017
DOI: 10.1089/dia.2016.0407
|View full text |Cite
|
Sign up to set email alerts
|

An Amperometric Glucose Sensor Integrated into an Insulin Delivery Cannula: In Vitro and In Vivo Evaluation

Abstract: Considering in vitro and in vivo findings together, it became clear that the mechanism of interference is the oxidation, at high bias potentials, of phenolic preservatives present in insulin formulations. This effect can be avoided by the use of redox mediator chemistry using a low bias potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Hence, with such a design, high friction forces generated during the insertion process may increase the probability of sensor failure. For example, following insertion into adipose tissue of swine, Ward et al observed fractures or short circuits in approximately one third of their electrochemical glucose sensors integrated onto the outer cannula walls [28]. To reduce the probability of experiencing such structural integrity issues Rumpler et al pre-punctured the human skin with a large gauge needle prior to inserting the device [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, with such a design, high friction forces generated during the insertion process may increase the probability of sensor failure. For example, following insertion into adipose tissue of swine, Ward et al observed fractures or short circuits in approximately one third of their electrochemical glucose sensors integrated onto the outer cannula walls [28]. To reduce the probability of experiencing such structural integrity issues Rumpler et al pre-punctured the human skin with a large gauge needle prior to inserting the device [29].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted under hospital settings, the glucose sensing accuracy of the single-port device was evaluated in type 1 diabetes subjects without however administering any insulin via the device [29]. In other in vivo studies, the glucose sensing accuracy of the single-port devices was assessed in anesthetized swine during either constant basal insulin delivery [15], [34], [35] or following the administration of bolus insulin [28], [34]. The MARD values reported in these studies ranged from 13.5% to 22.5% [15], [28], [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional barriers to AP use in young children include the limited amount of body surface area and adequate sites to wear two devices, 31 as well as frequent skin reactions and site failures in these patients. [32][33][34] Improved technologies, including a combined insulin infusion set and CGM sensor, 35 show promise and will be of great importance in this population. Finally, the use of AP algorithms that have been designed and tested in adults may not be appropriate for the management of very young children with T1D.…”
Section: Diabetes Technology and Therapeuticsmentioning
confidence: 99%
“…In this issue of Diabetes Technology and Therapeutics, Ward, et al present preclinical results on a comprehensive series of CGM studies focused on the development of a single site combined IIS and CGM sensor device. 14 The need to wear two separate devices when conducting sensor augmented pump or AP therapy has been frequently raised as a barrier by patients in clinical care and during research studies. Previously held assumptions about combined devices have reasoned that measuring glucose at the insulin delivery site will result in inaccurate CGM values due to the local effects of insulin.…”
mentioning
confidence: 99%